Speckle tracking echocardiography in plasma cell disorders: the role of advanced imaging in the early diagnosis of AL (Light Chain) cardiac amyloidosis. (3rd October 2022) - De Carli, G; Mandoli, G E; Sciaccaluga, C; Biagioni, G; Marallo, C; Turchini, F; Ghionzoli, N; Melani, A; Barilli, M; Pastore, M C; Gozzetti, A; Giacomin, E; et al.
Abstract: Introduction: Cardiac involvement is described as the most important prognostic factor in light chain amyloidosis. An early diagnosis is mandatory to customize the follow-up timing and the best treatment. The aim of the study was to identify the role of advanced echocardiography in the diagnosis of amyloid light chain cardiac amyloidosis (ALCA). Material and methods: Seventy-seven patients were prospectively included in the study: 22 patients with biopsy proven ALCA, 28 patients with multiple mieloma, and 27 with monoclonal gammopathy of undetermined significance. All patients underwent first and second level imaging including Speckle Tracking and complete biochemical profile. Univariate and Multivariate analysis was applied to the best multi-chamber predictor assessed with Receiver Operating Curve analysis. Continuous variables were discretized and compared with different subgroups based on multiparametric imaging assessment using available AL score. Results: Biochemical indices have been confirmed as the best predictors of ALCA. More specifically, high sensitivity troponin (hsTn) and N-terminal pro brain natriuretic peptide (NT-pro-BNP) showed an AUC of 0.88 and 0.91 respectively. Among left ventricular systolic function parameters, left ventricular longitudinal strain (AUC: 0.92); apical sparing pattern (AUC: 0.75) and relative wall thickness (RWT) (AUC: 0.88) showed the best diagnostic accuracy. Atrial parameters such as left atrial volume index (LAVI) (AUC: 0.74), left atrial stiffness (LAS) (AUC: 0.82) and inter-atrial septum diameter (AUC: 0.75) showed a good diagnostic accuracy in ALCA (Figure 1). LAS and AL score maintained their diagnostic value in the multivariate model analysis (B=2, 16; p=0, 01 and B= 0, 72; p<0.01 respectively). However, only LAS, with a cut off value of 0.65, was able to discriminate ALCA when AL score was not detrimental (P<0.001). Conclusion: ALCA diagnosis often relies only on the biochemical profile. A comprehensive cardiac evaluation by a multiparametric imaging approach with LAS estimation is mandatory to ensure early diagnosis and a prompt treatment through a multidisciplinary team assessment. Funding Acknowledgement: Type of funding sources: None.